The Effect of Cooperative Learning Model of The Type Inside Outside Circle and The of Bamboo Dancing On Student’s Learning Outcomes - Zalmita, Novia; Indani, Dita (Universitas Pendidikan Indonesia, 2021)
One of the efforts that can be done to achieve the learning objectives is by applying a learner-centered learning model such as the inside outside circle type cooperative learning model and the bamboo dancing type. Thus, this study aims to see the effect of the type of cooperative learning model inside outside circle and type of bamboo dancing on learning outcomes. The population in this study were students of class VIII SMPN 6 Banda Aceh. Sampling was done by purposive sampling technique by taking only two classes. The research method uses a quantitative approach with the type of experimental research design, none equivalent groups pretest-posttest design. Data were collected through the provision of multiple-choice tests to students. The results showed that tcount tTable (3.48 1.67). Thus Ha is accepted, so it can be concluded that the learning outcomes of students who are taught using the Inside Outside Circle learning model are better than the Bamboo Dancing learning model.